Donor lymphocyte infusion leads to diversity of specific T cell responses and reduces regulatory T cell frequency in clinical responders - Hofmann, Susanne; Schmitt, Michael (International journal of cancer, 2019)
T cell responses against malignant cells play a major role in maintaining remission and prolonging overall survival in patients after allogeneic stem cell transplantation and donor lymphocyte infusion (DLI) due to graft-versus-leukemia effect. For better characterization of the T cell responses, we assessed frequency and diversity of leukemia-associated antigen (LAA)-specific cytotoxic T cells using ELISpot and pMHC multimer assays and analyzed the frequency of regulatory T cells (Treg) as well as cytokine profiles before/after DLI. The data were correlated to the clinical course of patients. Significantly more LAA-derived T cell epitopes (p = 0.02) were recognized in clinical responders (R) when compared to nonresponders (NR). In addition, pMHC multimer-based flow cytometry showed a significantly higher frequency of LAA-specific T cells in R versus NR. The frequency of Treg in R decreased significantly (p = 0.008) while keeping stable in NR. No differences in T cell subset analysis before/after DLI were revealed. Clinical responders were correlated to specific immune responses and all clinical responders showed an increase of specific immune responses after DLI. Cytokine assays using enzyme-linked immunosorbent assay showed a significant increase of IL-4 after DLI. Taken together, an increase of specific CTL responses against several LAA after DLI was detected. Moreover, this study suggests that enhanced LAA diversity in T cell responses as well as decreasing numbers of Treg contribute to clinical outcome of patients treated with DLI.